MEMBANGUN GENERASI LITERASI DALAM PENDIDIKAN NON FORMAL DI BADAN OTONOM DI PONDOK PESANTREN MAMBAUL ULUM BATA-BATA - Moh. Hafidurrahman; Khoirul Anam; Mufiqur Rahman (Jurnal Pema Tarbiyah, 2022)
This paper thoroughly covered what PKN participants of IAI Al-Khairat Pamekasan Posko 17 have done. As we know, the first verse of the Al-qur'an that came down was iqro 'which means read. Departing on the basis of this verse, PKN Participants had initiated the development of creating literacy in non-formal education at Pondok pesantren Mambaul Ulum Bata-Bata and make this program a superior program initiated by PKN Posko 17 participants. Many steps and efforts to take attitudes and actions to create Islamic boarding schools with literacy culture have received positive responses from various stakeholders in the PKN place, especially from the head of Pondok pesantren. They are very enthusiastic in efforts to improve the literacy culture for students or santri. The final point of this activity is creating the formation of literacy groups that are active in non-formal institutions in Pondok Pesantren Mambaul Ulum Bata-Bata